Restaurant Tax Collection Policy in Support of Increasing Regional Income in Gorontalo Regency - Rusli Isa; Yanti Aneta (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to analyze the policy of collecting restaurant taxes to increase local revenue (PAD) in Gorontalo Regency. This study uses a qualitative descriptive method with primary and secondary data types. The focus of this research is optimizing government policies for collecting restaurant taxes in Gorontalo District. The results of the study show that government policies for collecting restaurant taxes are generally good but not yet effective in increasing local revenue (PAD). This can be seen from the indicators: achieving goals, integration, and adaptation used in capturing data in instruments to achieve maximum goals have not optimally contributed to local tax revenues, especially in the last two years. At the integration stage, in this case, the methods and approaches used during the socialization process have not yielded optimal results, which is evident in the lack of awareness among taxpayers about paying restaurant taxes. Meanwhile, for adaptation, especially the infrastructure or electronic transaction tools used to control and monitor the amount of tax revenue, not all of them can operate the equipment. The low level of public awareness of paying restaurant taxes can be seen from the fact that there are still some people who do not understand the benefits of restaurant taxes as a source of local revenue for Gorontalo Regency.